Determination of the concentrations and the chemical composition of particulate matter in the North Aegean region - Τριανταφύλλου, Ελένη; Triantafyllou, Eleni (2022)
Particulate matter (PM) pollution is a major environmental problem in urban and remote areas, as it causes adverse effects upon human health and affects directly or indirectly the climate of the Earth. PM can vary considerably in size, chemical composition and origin. Therefore, numerous studies have investigated particle pollution exposure and its effects around the globe, including the region of the Eastern Mediterranean, which is considered a climate change hotspot that is affected by transportation of air pollutants originating from Europe, Africa and Asia. Despite these studies, however, there is still insufficient information on the air quality of insular coastal areas on the northern part of Eastern Mediterranean, i.e., the Northern Aegean Sea (NAS), and on the contribution of the local and the distant sources that influence it.